Perpustakaan Umum Di Kota Dumai Dengan Penekanan Pencahayaan Alami - Saputra, Riko Mardi; Hidayat, Wahyu; Susilawati, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Public library is a real place for community to meet the need for information. Reading activities as the main activity in the library have the most important factors to be considered, that is in terms of lighting. Indonesia is a tropical country that gets sunshine all year round, so the availability of natural light is very abundant. The natural sunlight can be used to meet the lighting needs of public libraries, keeping in mind the activities that take place therein are daylight. The concept of “lantern” is used as an effort to integrate function and theme. The formula is to provide a slim form of the building, advance the facade, the formation of triangles, and atrium so that the surface area to respond for natural lighting can be optimal. So that through the surface can be given openings to insert light from the side and above. In the application, the resulting design has wide openings on the sides of the building, the anticipation of light and overheating is done by sunscreen placement on the north and south sides. The application of this concept produces a library that is rich in natural light but remains comfortable and safe for users which refers to the standard of lighting in space for public libraries, so that incoming lighting can have a good impact on space, users, and library materials.Keywords: Library, Public Library, Lighting, Natural Light.